Islamic Education Planning and Its Implications for the Learning of Kitab Kuning in Islamic Boarding Schools - Mustaqim, Mustaqim; Razy, Fakhrur; Mardhatillah, Aufatus Syakira; Syahweli, Fahril; Ilmi, Darul (STIT Ahlussunnah Bukittinggi, 2025)
This article explores the fundamental concepts, scope, and urgency of Islamic education planning in addressing contemporary challenges. Islamic education planning is understood as a systematic and continuous process aimed at establishing high-quality, relevant institutions grounded in Islamic values. The study employs a qualitative library research approach, enriched by interviews with leaders, teachers, and students in Islamic boarding schools. Data were collected from academic literature and analyzed using content analysis to identify key themes related to Islamic education planning. The findings reveal that well-structured planning serves as a crucial strategy for directing education, optimizing resources, and enhancing the quality of Kitab Kuning learning. Consequently, Islamic educational institutions are better positioned to cultivate knowledgeable, virtuous, and globally adaptive generations.